MARKETING STRATEGIES FOR ENTERING THE GLOBAL JEWELRY MARKET (Marketing Journal, 2026)
This article examines the current state of the global jewelry market, its development trends, and marketing strategies for entering international markets. The study analyzes the regional concentration of the global jewelry market, the market share of leadi ng countries, and key changes in the precious metals market. Particular attention is paid to market segmentation, brand positioning, pricing strategies, distribution channels, and the role of digital marketing tools in entering the global jewelry market. T he research findings indicate that successful market entry requires a systematic and adaptive marketing approach.
Keywords: global jewelry market; marketing strategies; market entry; jewelry products; digital marketing; brand positioning. № 1 -SON YANVA R; 202 6-YIL 215